The influence of tectonics on underwater morphology of the Arafura Sea by using seismic refraction in West Papua, Indonesia - Jusfarida, Jusfarida; Wijaya, P Hadi; Syafri, Idriem; Hardjana, Budhi (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2022)
The Arafura waters are part of the northern edge of the Mesozoic Passive Margin of Australia. The movement of plates on the ocean floor results in the formation of reliefs on the seabed, these reliefs are commonly referred to as seabed morphology. Tectonic activity on the Tarera-Aiduna fault, until now still plays an important role and controls conversion tectonic activity in this area. Collision between plates or subduction is the eventuality quality of a collision between plates, where one plate plunges downwards, forming an ocean trench. The seabed is a very deep and narrow seabed, the walls are steep and steep with a depth of more than 200 m. The purpose of this study was to determine the morphological formations on the seabed caused by tectonic activity, so as to obtain what tectonic processes are working in the area. The method used in this research is to analyze the data generated by the survey ship Geomarine III, owned by P3GL, Ministry of Energy and Mineral Resources. The data used are Marine seismic data and Bathymetry data, analysis of seismic data is intended to determine rock layers, and the geometric shape of the structures that develop in the area, while Bathymetric data analysis is intended to determine the depth of sea water, which is also used to determine reliefs. Or morphology under the seabed. The results of the analysis are in the form of morphological formations on the ocean floor starting from the Exposure area to the Aru Trench.